2015
DOI: 10.1038/mi.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin beta receptor signaling limits mucosal damage through driving IL-23 production by epithelial cells

Abstract: The immune mechanisms regulating epithelial cell repair after injury remain poorly defined. We demonstrate here that lymphotoxin beta receptor (LTβR) signaling in intestinal epithelial cells promotes self-repair after mucosal damage. Using a conditional gene-targeted approach, we demonstrate that LTβR signaling in intestinal epithelial cells is essential for epithelial IL-23 production and protection against epithelial injury. We further show that epithelial-derived IL-23 promotes mucosal wound healing by indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 50 publications
(81 reference statements)
8
71
1
Order By: Relevance
“…IL-1β and TNF-α stimulation induces IL-23p19 production by synoviocytes [6]. LPS stimulation of TLR4 or ligation of agonistic antibody to LTβR in the colon epithelial cell line stimulates IL-23 production [4]. Similarly, colon epithelial cells, in situ, were shown to produce IL-23 in an LTβR-dependent fashion.…”
Section: Il-23 Stimulatory Ligandsmentioning
confidence: 94%
See 1 more Smart Citation
“…IL-1β and TNF-α stimulation induces IL-23p19 production by synoviocytes [6]. LPS stimulation of TLR4 or ligation of agonistic antibody to LTβR in the colon epithelial cell line stimulates IL-23 production [4]. Similarly, colon epithelial cells, in situ, were shown to produce IL-23 in an LTβR-dependent fashion.…”
Section: Il-23 Stimulatory Ligandsmentioning
confidence: 94%
“…Epithelial cells were also shown to contribute to IL-23 production. These include keratinocytes [3], intestinal epithelial cells [4] and glomerular podocytes (epithelial cells in the Bowman's capsule especially during nephrotoxic serum (NTS) nephritis (NTN)) [5]. Furthermore, human fibroblast-like synoviocytes (ex vivo and in vivo) and human colon subepithelial myofibroblasts were shown to produce IL-23p19 upon IL-1β and TNF-α all of which suggest that non-hematopoietic sources may also contribute to IL-23 production to some extent, given the right stimulation [6,7].…”
Section: Cellular Sources Of Il-23mentioning
confidence: 99%
“…In fact, epithelial cells produce antibacterial RegIII proteins which are necessary for protection against C. rodentium (Zheng et al, 2008;Gallo and Hooper, 2012;Abt and Pamer, 2014;Mukherjee et al, 2014). Recent studies revealed that coordinated cross-talk between gut epithelial cells, RORγt + ILCs, DCs and macrophages is necessary for mucosal healing, control of commensal microbiota and for generation of effective immune responses against gut pathogens (Kruglov et al, 2013;Belkaid and Hand, 2014;Longman et al, 2014;Macho-Fernandez et al, 2015;Mortha et al, 2014). Therefore, the ability to isolate primary intestinal epithelial cells and lymphoid cells from the gut during infection is key in understanding the molecular mechanisms of immune cellmediated mucosal protection.…”
Section: Isolation Of Epithelial Cells and Intestinal Lymphoid Cells mentioning
confidence: 99%
“…1a and (Satoh-Takayama et al, 2008;Wang et al, 2010)). The protective mechanism by which RORγt + ILCs mediate mucosal protection includes expression of surface heterotrimeric lymphotoxin (LTβ2LTα1) which signals via lymphotoxin beta receptor (LTβR) on DCs, macrophages and epithelial cells to induce production of IL-23 (Wang et al, 2010;Tumanov et al, 2011;Macho-Fernandez et al, 2015). IL-23, in turn, activates IL-23R on ILCs to produce IL-22 which signals via IL-22R on intestinal epithelial cells to drive the expression of antibacterial proteins and promote epithelial barrier integrity and epithelial cell regeneration via a STAT3-dependent mechanism (Sugimoto et al, 2008;Cella et al, 2009;Grivennikov et al, 2009;Pickert et al, 2009).…”
Section: Commensal Microbiotamentioning
confidence: 99%
“…The cue for this process is provided by IL-23 produced by the epithelial cells. IL-23 induces IL-22 mediated, cell proliferation and increased mucous secretion by a group of lymphoid tissue inducer cells expressing CCR6 and RORγt [43].…”
Section: The Effect On Intestinal Epithelial Cellsmentioning
confidence: 99%